Pupil's president A. P. J. Abdul Kalam - Roychowdhury, Satyam (ed) (Bee Books, 2018)
Pupil's president A. P. J. Abdul Kalam / Roychowdhury, Satyam (ed). -- Kolkata: Bee Books, 2018 954.0532092 K14e10 10th ed No. of Copies : 1